INVESTIGATION OF HEALTH SERVICE EFFICIENCY OF METROPOLITANS IN TURKEY BY DATA ENVELOPMENT ANALYSIS METHOD (Third Sector Social Economic Review, 2024)
In today's globalizing world, it is extremely important in terms of individual and public health that the rapidly developing and changing health systems can be offered with limited resources in a way that will provide the highest benefit. Effective use of resources in the health sector, reducing inactive use and providing a better health service require performance measurement. In this context, the aim of the research is to determine the effectiveness of health institutions operating in Turkey on a metropolitan basis using health indicators, to determine the inefficiency of metropolitan cities that are not at the efficient border, to calculate their idle use and to determine the super efficiency values of effective metropolitan cities. In the study in which 4 input and 3 output variables were used, 27 metropolitan cities were included in the analysis and efficiency calculations were made on the basis of metropolitan cities. In this direction, data from the 2020 Ministry of Health Health Statistics Yearbook were used and R Studio package programs were used to analyze the research data. As a result of the research, 7 metropolitan cities were determined as efficient according to the CCR model, while 14 metropolitan cities were determined as effective according to the BCC model. In addition, it has been seen that Mardin is the most effective metropolitan city among the active metropolitan cities.
Keywords: Data Envelopment Analysis; Metropolitans; Healthcare; Efficiency